The ‘AI-Powered’ Madrasa: Efficacy of Personalized AI Tutors for Qur’anic Memorization and Arabic Language Learning - Syarifatul Hayati Zarfi; Ali Omar; Samira Mohammed (Islamic Studies in the World, 2025)
The integration of artificial intelligence (AI) into Islamic education has introduced new opportunities for enhancing Qur’anic memorization (tahfiz) and Arabic language learning through personalized, adaptive technologies. Traditional madrasa models rely heavily on direct teacher–student interaction, repetition-based practice, and individualized correction, yet often face constraints related to limited teaching time, large class sizes, and diverse learner abilities. Recent advancements in AI-driven tutoring systems provide alternative pathways for supporting memorization accuracy, pronunciation refinement, and grammar acquisition, offering a scalable solution aligned with contemporary educational needs. This study aims to evaluate the efficacy of personalized AI tutors in improving Qur’anic memorization performance and foundational Arabic language competency among madrasa students. The research investigates how AI-generated feedback, adaptive pacing, and real-time voice recognition contribute to learner progress, motivation, and error reduction within tahfiz and language-learning contexts. A quasi-experimental design was employed involving two groups: an experimental group using AI-powered tutoring applications and a control group engaging in conventional instructional methods. Data were collected through pre-tests and post-tests in Qur’anic memorization fluency, tajw?d accuracy, and basic Arabic vocabulary and grammar assessments. Additional qualitative data were gathered from student reflections and teacher interviews. The results demonstrate that students in the AI-assisted group achieved significantly higher gains in memorization retention, pronunciation accuracy, and vocabulary mastery compared to the control group. Learners also reported increased engagement, reduced anxiety, and enhanced autonomy in their study routines. The findings highlight the pedagogical value of AI tutors in complementing traditional madrasa teaching practices. The study concludes that AI-powered personalized tutoring systems can serve as effective supplementary tools for Qur’anic and Arabic instruction, provided that implementation aligns with ethical, pedagogical, and cultural considerations.